Comparison of Condylar Bone Density in Cone-Beam Computed Tomographic Images of Patients with and without Temporomandibular Joint Disorders - Maryam Eisazadeh; Leila Khojastepour; Abdolaziz Haghnegahdar; Parisa Soltani (Wolters Kluwer Medknow Publications, 2021)
Introduction: Temporomandibular disorders (TMDs) are the main source of orofacial pain of nondental origin. Density changes in mandibular condyles of patients with TMD have not been well documented. The aim of this study was to compare condylar head bone density values in patient with and without TMD in cone-beam computed tomographic (CBCT) images. Materials and Methods: CBCT images of 70 patients with TMD and 70 age- and sex-controlled individuals were studied. Density of the cancellous bone in the left and right condylar heads was measured on a CBCT slice with the widest mediolateral dimension. Moreover, absence of at least one maxillary or mandibular posterior tooth (except for third molars) was recorded. Interclass correlation, t test, and Chi-squared test were used for statistical analysis. Results: Bone density in the condylar head significantly increased in patients with TMD compared with the non-TMD group (P < 0.001). The difference between males and females in each group was not significant (P = 0.182). Condylar head bone density in patients with TMD with posterior missing teeth was significantly less than individuals without missing teeth (P = 0.002). Conclusion: Increased density of condylar head must be regarded as a potential diagnostic tool for TMD when interpreting CBCT images of the joints.